2017
DOI: 10.1177/0009922817728698
|View full text |Cite
|
Sign up to set email alerts
|

Stock Photographs Do Not Comply With Infant Safe Sleep Guidelines

Abstract: We evaluated images in popular stock photography websites for adherence with American Academy of Pediatrics (AAP) guidelines for safe infant sleep practices. Three top stock photo websites were used to collect photographs generated from key phrases. All images depicting an infant sleep environment were analyzed for consistency with AAP guidelines. Descriptive statistics, chi-square and z test of proportions, were conducted. A total of 1233 of 1947 stock photographs showed sleeping infants on a flat surface. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Despite these valuable channels for communicating the safe sleeping advice, we don't seem to take the current power and influence of the internet into account sufficiently. Many pictures contradict the safe sleeping advice on popular websites, in blogs, in ads, and on social media ( 20 , 21 ). These pictures influence the behavior of young parents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these valuable channels for communicating the safe sleeping advice, we don't seem to take the current power and influence of the internet into account sufficiently. Many pictures contradict the safe sleeping advice on popular websites, in blogs, in ads, and on social media ( 20 , 21 ). These pictures influence the behavior of young parents.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, popular infant care trends like sharing a sleep surface with an infant, shared on the internet and shown in magazines, may also influence the behavior of parents. A major part of the images online and in magazines do not adhere to the infant safe sleeping guidelines ( 20 , 21 ). When the prevalence of behavior contrary to safe sleeping advice increases over time, a rise in SUDI incidence might also be expected.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we opted to study the images found in stock photographic databases. These are the most intensely used resources for journalists, website editors, and even academic institutions ( Frosh, 2001 ; Goodstein et al., 2018 ). They are used to obtain illustrative medical images for conditions including pediatric mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The pictures used online to illustrate articles are often supplied by stock photography databases ( Frosh, 2001 ). These provide royalty-free photos to websites, advertisers or health institutions, including hospitals and other health care providers ( Goodstein et al., 2018 ). Website editors and designers will select images to display, without medical experience or the use of epidemiological data.…”
Section: Introductionmentioning
confidence: 99%
“…A large majority of infant deaths occur due to sudden unexpected infant deaths (SIDS), which generally occurs during sleep and mostly due to an unsuitable sleep environment, within the first year of life [1][2][3]. In the USA, nearly 3,500-4,000 babies die due to sleep-related SIDS each year [4][5][6][7]. The Center for Disease Prevention and Control reported that SIDS is among the top three causes of infant deaths, and in 2018, approximately 1,300 infant deaths occurred due to SIDS, 1,300 due to unknown causes and 800 due to accidental suffocation and strangulation in bed [8].…”
Section: Introductionmentioning
confidence: 99%